The Grammar of Ornamentation: An Egyptian Predynastic Decorative Continuum - Beuthe, Tatjana (Studia Orientalia Electronica, 2022)
Tags made of mudstone are predominantly found in ancient Egyptian Predynastic cemetery contexts. This study examines the symbolism and significance of mudstone tags with the recurved horns of hartebeests and crescent-shaped mudstone tags. The use of syncretic imagery on these tags provides evidence for the fluidity of artistic perceptions in Predynastic Egypt. Available data suggests that individuals buried with mudstone hartebeest and crescent tags were almost exclusively female. Evidence for use wear and the find locations of the tags in burials indicates these artefacts were likely associated with rituals performed by female individuals.